2013
DOI: 10.1088/2041-8205/775/1/l11
|View full text |Cite
|
Sign up to set email alerts
|

STELLAR ROTATION PERIODS OF THE KEPLER OBJECTS OF INTEREST: A DEARTH OF CLOSE-IN PLANETS AROUND FAST ROTATORS

Abstract: We present a large sample of stellar rotation periods for Kepler Objects of Interest (KOIs), based on three years of public Kepler data. These were measured by detecting periodic photometric modulation caused by star spots, using an algorithm based on the autocorrelation function (ACF) of the light curve, developed recently by McQuillan, Aigrain & Mazeh (2013). Of the 1919 main-sequence exoplanet hosts analyzed, robust rotation periods were detected for 737. Comparing the detected stellar periods to the orbita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
272
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(294 citation statements)
references
References 37 publications
19
272
2
Order By: Relevance
“…We failed to find any close-in planet around fast-rotating stars, confirming the results obtained by McQuillan et al (2013b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We failed to find any close-in planet around fast-rotating stars, confirming the results obtained by McQuillan et al (2013b).…”
Section: Discussionsupporting
confidence: 91%
“…All of them are single systems to the best of our knowledge. By studying P rot as a function of the orbital period of the innermost planet, we found that there are no close-in planets around fast rotators in this small sample of asteroseismic targets, as pointed out by McQuillan et al (2013b). The study of the KOI light curves requires a specific analysis to properly remove the transit signature without affecting the rotation modulation.…”
Section: Discussionmentioning
confidence: 60%
“…In the case of Kepler-49 c, the models and transit shape are consistent with a near-grazing (b∼0.9) model. The host is known to be an active star with a likely rotation period of∼18.5 days (McQuillan et al 2013). We speculate that Kepler-49 c was seen to be consistently crossing a polar star spot resulting in a diluted transit depth.…”
Section: Stellar Parametersmentioning
confidence: 84%
“…In agreement, Walkowicz & Basri (2013) reported a rotation period of P = 33.26 ± 3.44 days for this star, based on the analysis of quarter 9 data alone. On the other hand, McQuillan et al (2013) did not find a significant period for this star from the auto-correlation function on quarter 3−14 data. This periodicity could be interpreted as the rotational period because it is present identically in the first and second halves of the light curve.…”
Section: Primary Star Parametersmentioning
confidence: 62%